(SA (BShort Calculus / An Applied Approachs - Saltz Daniel (Scott, Foresman And Company, 1985)
Functions and Graphs and Limits, The Derivative, Extremum Problems and Curve Sketching, Exponential and Logarithmic Functions, Integration, Applications of the Integral, Multivariable Calculus, Differential Equations, Maclaurin Taylor Polynomials; Sequences and Series, The Trigonometric Functions, Appendix: A Review of Algebra, Answers to Odd-Numbered Exercises, Index.